2009
DOI: 10.5194/angeo-27-2503-2009
|View full text |Cite
|
Sign up to set email alerts
|

West African equatorial ionospheric parameters climatology based on Ouagadougou ionosonde station data from June 1966 to February 1998

Abstract: Abstract. This study is the first which gives the climatology of West African equatorial ionosphere by using Ouagadougou station through three solar cycles. It has permitted to show the complete morphology of ionosphere parameters by analyzing yearly variation, solar cycle and geomagnetic activity, seasonal evolution and diurnal development. This work shows that almost all ionospheric parameters have 11-year solar cycle evolution. Seasonal variation shows that only foF2 exhibits annual, winter and semiannual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…During sunrise, the magnetic flux tubes again filled up because of their small volume, resulting in a sudden increase in ionization due to increasing thermospheric temperatures during sunrise (Oron et al, 2013). The observed nighttime GPS TEC enhancement could be attributed to the tidal winds, which blow the ionization across the geomagnetic field.…”
Section: Hourly Variation In Gps Tec Across Longitudesmentioning
confidence: 93%
“…During sunrise, the magnetic flux tubes again filled up because of their small volume, resulting in a sudden increase in ionization due to increasing thermospheric temperatures during sunrise (Oron et al, 2013). The observed nighttime GPS TEC enhancement could be attributed to the tidal winds, which blow the ionization across the geomagnetic field.…”
Section: Hourly Variation In Gps Tec Across Longitudesmentioning
confidence: 93%
“…This is related to winter maximum of O atoms, implying the relative increase of light gases above the winter hemisphere (Scialom, 1974), due to dynamic influences in the thermosphere (Rishbeth and Müller-Wodarg, 2006). Ouattara et al (2009) propose to explain the absence of the winter anomaly during cycle 20 by the influence of fluctuating wind stream activity.…”
Section: Annual and Semiannual Variationsmentioning
confidence: 99%
“…The difference in the correlation coefficients from one sunspot cycle to another can be explained by changes in the solar cycle intensity (Balan et al, 1993). Ouattara et al (2009) found for Ouagadougou, located at the magnetic equator in the Northern Hemisphere, a good correlation between the sunspot number and foF2, foF1, and h F1, but no correlation for foE, h F2 and h E. The absence of correlation between the sunspot number and foE at the equator can be explained by the existence of the equatorial electrojet, which drives instabilities and generates strong plasma waves which strongly affect the electron density (Farley, 2009). …”
Section: Solar Cycle Variationsmentioning
confidence: 99%
See 2 more Smart Citations